Determinan Loyalitas Konsumen Le Minerale di Jakarta: Peran Kualitas Produk dan Citra Merek - Ambo Sakka Hadmar (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2021)
This article discusses the research entitled the influence of product quality and brand image on consumer loyalty of Le Minerale in Jakarta. The research object selected was 123 respondents, namely consumers who often buy bottled water using purposive sampling technique. The approach chosen is quantitative associative, which is a research method that analyzes the relationship between two variables. Data was collected by distributing questionnaires via google form with a Likert scale that functions to measure each question item. Data analysis techniques using validity, reliability, classical assumptions, multiple regression, correlation, determination, t test and F test (Anova). The results showed that both product quality and brand image variables partially and simultaneously had a positive and significant effect on consumer loyalty.